2014
DOI: 10.4209/aaqr.2013.07.0239
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Airborne Nanoparticle Filtration and Thermal Rebound Theory

Abstract: This paper provides an overview of recent studies on the filtration of airborne nanoparticles. Classical filtration theory assumes that the efficiency of nanoparticle adhesion is at unity when nanoparticles strike a filter with a Brownian motion. However, it has been pointed out that small nanoparticles may have a sufficiently high impact velocity to rebound from the surface upon collision, a mechanism called thermal rebound. According to thermal rebound theory, the adhesion efficiency of nanoparticles decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 130 publications
(177 reference statements)
1
20
0
Order By: Relevance
“…This result suggests that capture by electrostatic forces is important for particles in the 250–300-μm range. Overall, filters appear to behave in a manner consistent with theoretical predictions that common filter materials allow for efficient collection through diffusion of nanoparticles down to 2 nm (Givehchi and Tan 2014). …”
Section: Resultssupporting
confidence: 70%
“…This result suggests that capture by electrostatic forces is important for particles in the 250–300-μm range. Overall, filters appear to behave in a manner consistent with theoretical predictions that common filter materials allow for efficient collection through diffusion of nanoparticles down to 2 nm (Givehchi and Tan 2014). …”
Section: Resultssupporting
confidence: 70%
“…The coefficient of restitution for nanoparticles is not unity, and the absolute value is unknown for nanosized particles (Ayesh et al, 2010;Givehchi & Tan, 2014;Sato, Chen, & Pui, 2007;Wall, John, & Wang, 1990). The coefficient of restitution varies with the material of the nanoparticles, the filter media, and the impact velocity of the nanoparticles.…”
Section: Thermal Rebound Effectmentioning
confidence: 99%
“…However, these parameters are unknown for most nanomaterials (Givehchi & Tan, 2014). In addition, more and more studies have shown that the material properties of nanoscale materials differ from those of bulk materials (Gu, Krauss, Steurer, Gramm, & Cervellino, 2008;Rennecke & Weber, 2013b).…”
Section: Thermal Rebound Effectmentioning
confidence: 99%
“…However, this appears not always to be the case, and below a very small size (1 nm), NP tend to behave essentially as molecules and appear to be affected by a thermal rebound effect that causes them to detach from the filter fibers [51]. Givehchi and Tan [68] have devoted a study to the matching of currently used mathematical models with experimental results and noted that the validity of the single fiber model as a theory of filtration is weak and that the model does not take into consideration all of the phenomena that come into play.…”
Section: Means Of Containmentmentioning
confidence: 99%
“…Small NPs may rebound from the filter surface if their kinetic energy is high enough to overcome the adhesion energy. Until now, published studies have not shown whether this effect is important or not [68]. The inevitable steady decline in HEPA filter effectiveness and performance must also be managed properly with regular replacement [80] and disposal procedures for HEPA filters must be in place.…”
Section: In the Current Context What Engineered Control Measures Shomentioning
confidence: 99%